Exercícios formativos da práxis benincaniana : diálogo e memória em sala de aula - Scartezini, Angela Trombini (2023)
The research aims to investigate listening, dialogue and writing of class memory as formative exercises of benincaniana praxis and understand how they contribute to the training of teachers and students, resignifying the contemporary school pedagogical practice. The central question is formulated as follows: "In what sense are the formative exercises of listening, dialogue and elaboration of class memory transforming sources of pedagogical practice in the classroom and of the subjects involved in the pedagogical process?" To account for this, the texts of Elli Benincá and his research group are consulted; two works elaborated by scholars from his life and work, the work itself and the pedagogical legacy of the author, as well as texts by authors such as Masschelein and Simons, Larrosa, Biesta, Foucault and Dalbosco. Benincá and the other authors consulted in the course of this dissertation bring the need to study the philosophical and pedagogical principles of Greco-Roman antiquity, especially the texts of moral philosophy and literature, pointing to the danger linked to the abandonment of the classics. Reading Benincá in articulation with classical and contemporary texts renews, updates and enhances your thinking. Based on the hermeneutic methodological procedure, the research is bibliographic in nature, qualitative, elaborated from a literature review and organized in four chapters. The first brings a brief account of the author's formative journey to the encounter with the work and legacy of Benincá, presenting and contextualizing briefly the architecture that composes her praxis. This chapter also presents the research methodology and the investigative path. The second chapter understands and contextualizes the school and the human being through a contemporary school diagnosis. Next, the third chapter investigates listening and dialogue as classic hermeneutical presuppositions of benincaniana praxis. In turn, the fourth chapter reflects the exercises of reading and writing class memories as a formative pedagogical posture and as an important source of critical resistance to the excellence administered in the school space. Benincaniana praxis is characterized by collective formation and self-formation and comprises a methodological process of observation of practice – recorded and reflected in a systematic way. The practice of recording, the methodical rereading of the texts, the systematizations, the presentation with the peers, the rewriting and the dynamics of the question were structuring elements of benincaniana praxis. Thus, recognizing and starting from common sense, in order to re-signify it, is an ethical-epistemological task of the teacher/researcher committed to a project of transformative and inclusive society. Benincá believed it was possible to understand praxis as a permanent need for pedagogical action in the process of formation of educators, configuring itself as a possibility of understanding, assimilating and overcoming the contemporary challenges of teaching and human self-formation. As the main result of the research, the analysis of the selected texts leads to the understanding of the mystique cultivated by Benincá. In this, the exercises of listening, dialogue and writing of the class memory become a possible formative and pedagogical antidote when taken as unlearning of teaching while doing technical and bureaucratic of the contemporary school.